The wandering spleen torsion - Ravindra N Irpatgire; Dinkar Kale (International Journal of Medical Research and Review, 2015)
Wandering spleen is the absence of spleen at its normal left upper quadrant. It may be because of increased splenic mobility resulting from laxity or maldevelopment of the suspensary gastrosplenic, splenorenal, and phrenicocolic ligaments. Wandering spleen is prone for complications like trauma and torsion. Torsion is quite rare complication. Diagnosis of wandering spleen is quite difficult because of the lack of symptoms and signs until splenic torsion have occurred. Here we report an interesting case of a 16-year-old unmarried girl presenting with acute abdomen, diagnosed with wandering spleen torsion and managed surgically.